Biological features of TcM: A new Trypanosoma cruzi isolate from Argentina classified into TcV lineage - Martinez, Santiago Jose (2022)
Trypanosoma cruzi, the etiologic agent of Chagas disease (CD) presents a wide genetic and phenotypic diversity that is classified into seven lineages or discrete typing units (DTU: TcI to TcVI and Tcbat). Although isolates and strains that belong to a particular group can share some attributes, such as geographic distribution, others like growth rate, cell tropism, and response to treatment can be highly variable. In addition, studies that test new trypanocidal drugs are frequently conducted on T. cruzi strains maintained for a long time in axenic culture, resulting in changes in parasite virulence and other important features. This work aimed to isolate and characterize a new T. cruzi strain from a chronic Chagas disease patient. The behavior of this isolate was studied by using standard in vitro assays and in vivo mice infection tests and compared with the T. cruzi Y strain (TcY), broadly used in research laboratories worldwide. Data showed that TcM behaves as a slow-growing strain in vitro that develops chronic infections in mice and displays high tropism to muscular tissues, in accordance with its clinical performance. In contrast, the Y strain behaved as an acute strain that can infect different types of cells and tissues. Interestingly, TcM, which belongs to DTU TcV, is more susceptible to benznidazole than TcY, a TcII strain considered moderately resistant to this drug. These differential properties contribute to the characterization of a TcV strain, one of the main lineages in the southern countries of South America, and open the possibility to introduce changes that improve the management of Chagas patients in the future.